Validity and Reliability od Postgraduate Hospital Educational Environment Measure - Bahasa Indonesia Version - Natalia Widiasih Raharjanti; Adhitya Sigit Ramadianto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Educational environment is an essential factor influencing performance of medical residents, and unsupportive educational environment is associated with considerable harmful impacts. The Postgraduate Hospital Educational Environment Measure (PHEEM) is a self-administered questionnaire designed to measure residents’ perception of their educational environment. This study aims to establish the validity and reliability of PHEEM - Bahasa Indonesia version. Methods: The original PHEEM is translated and modified through an expert panel discussion. Construct validity is measured by corrected item-total correlation. Internal consistency reliability is measured by Cronbach’s alpha. Sample was taken from neurology and radiology residents. Results: The first validation trial was done on 44 neurology residents while the second trial was done in 35 radiology residents. Almost all item scores are correlated with the total score with r > 0,3. Cronbach’s alpha of PHEEM is 0,89 and 0,91 in the first and second trial, respectively.Conclusion: This is the first PHEEM validation study in Indonesia; changes to the instrument were made to maintain face and content validity. While the sample size is small and not selected randomly, PHEEM - Bahasa Indonesia version has acceptable validity and reliability to be used in research and evaluation of residency programs.